Bounds of unfair inequality of opportunity: Theory and evidence for Germany and the US - Judith Niehues; Andreas Peichl (Center for Economic Studies and ifo Institute (CESifo), 2012)
Previous estimates of inequality of opportunity (IOp) are lower bounds because of the unobservability of the full set of endowed characteristics beyond the sphere of individual responsibility. Knowing the true size of unfair IOp, however, is important for the acceptance of (some) inequality and the design of redistributive policies as underestimating the true amount of IOp might lead to too little redistribution. This paper is the first to suggest an upper bound estimator. We illustrate our approach by comparing Germany and the US based on harmonized micro data. We find significant, sizeable and robust differences between lower and upper bound estimates - both for gross and net earnings based on either periodical or permanent income - for both countries. We discuss the cross-country differences and (surprising) similarities in IOp in the light of differences in social mobility and persistence.
Keywords: D63; H20; J62; J70; 330; equality of opportunity; earnings inequality; mobility; circumstances; family background; redistribution